The singer’s voice a science and art integration - Guzmán, Marco (Revista Chilena de Fonoaudiología, 2006)
The phisiology and technique of the singed voice, is poorly understood by the voice therapists. To understand the processes involved, not only it is necessary theorical knowledge, but also an experimental personal practice. Base on this, it is possible to do a successfully voice treatment and evaluations, to singer patients who suffering voice disorders. In this rewiew are discussed the most important aspects of the singed voice, considering respiratory, emission and resonante parameters and its influence on the singed voice therapy.